1983
DOI: 10.1128/mcb.3.3.340
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular location of an abundant substrate (p36) for tyrosine-specific protein kinases.

Abstract: A 36,000-dalton cellular protein (p36) has been identified previously as an abundant substrate for phosphorylation by tyrosine-specific protein kinases. Since several of the responsible kinases are associated with the plasma membrane, we explored the subcellular distribution of p36. Biochemical fractionations located p36 on the plasma membrane of both normal and retrovirus-transformed cells. Approximately half of the p36 was bound to the membrane with the affinity of a peripheral membrane protein; the remainde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
1
1

Year Published

1983
1983
1990
1990

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(52 citation statements)
references
References 28 publications
3
47
1
1
Order By: Relevance
“…It is a relatively abundant protein, and upon transformation of the host cells by RSV, this protein becomes up to 10-fold more phosphorylated on tyrosine than in normal cells. Recent studies by several groups have revealed that the 36K protein is localized in the plasma membrane or the detergent insoluble matrix of the cell or both (8,14,19,32,41). In the transformed cell, only 5% of the total 36K protein is phosphorylated on tyrosine and the localization of this phosphorylated form appears to be no different from the major nonphosphorylated form, within the detection limits of the experiments.…”
Section: Resultsmentioning
confidence: 87%
“…It is a relatively abundant protein, and upon transformation of the host cells by RSV, this protein becomes up to 10-fold more phosphorylated on tyrosine than in normal cells. Recent studies by several groups have revealed that the 36K protein is localized in the plasma membrane or the detergent insoluble matrix of the cell or both (8,14,19,32,41). In the transformed cell, only 5% of the total 36K protein is phosphorylated on tyrosine and the localization of this phosphorylated form appears to be no different from the major nonphosphorylated form, within the detection limits of the experiments.…”
Section: Resultsmentioning
confidence: 87%
“…It has become evident from cell fractionation, morphologic and immunochemical studies that p36, or at least a fraction of it, is closely associated with plasma membranes (Cooper and Hunter, 1982;Amini and Kaji, 1983;Courtneidge et al, 1983;Nigg et al, 1983), with detergent-resistant cytoskeletal structures (Cheng and Chen, 1981;Cooper and Hunter, 1982) or, according to one study, with ribonucleoprotein particles (Arrigo et al, 1983). However, distinctly specific interactions, such as that of vinculin, another important tyrosine kinase substrate, and focal adhesion sites (Sefton et al, 1981), have not been found between p36 and other membrane or cytoskeletal components.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, once isolated, the 35-kDa substrate from A431 cells could serve as substrate for the EGF(Uro) receptor kinase in a reconstituted system. The 35-kDa substrate from A431-cell membranes appeared to differ from other potential EGF(Uro) receptor substrate(s) of comparable molecular mass (34-39 kDa) that have been detected in 32P-labeled cells after Rous sarcoma virus infection (19)(20)(21)(22)(23)(24)(25)(26)(27) and that have been isolated from intestinal epithelium (28). The relationships of the 35-kDa A431 substrate (19) and the 36-kDa intestinal substrate (28) to the G-protein f subunit remain to be determined.…”
Section: Discussionmentioning
confidence: 99%